Liberación miofascial de contracturas musculares isquiotibiales en futbolistas - Sanaguano Escudero, Hugo Santiago (2021)
ABSTRACT The following research developed by the bibliographic review method that exposed the use of Myofascial Release Therapy for hamstring contractures in soccer players. The muscles contractures are unintentional on the muscles, it occurs by excessive nerve stimulation, poor postures, or vicious posturing, direct or indirect trauma. The Myofascial release is a manual therapy that is based in the application of movements and sustained pressure that are directed to all fascial system releasing tensions and muscular contractures. The application of The Myofascial release technique on the country is low because the unknown benefices that causes on the soccer players that suffer muscular contractures hamstring, however of the 80 articles found. just 35 are appropriate for the study which were carefully selected by their inclusion and exclusion criteria, moreover of comply with a valuation equal or major to 6 according to the scale “Physiotherapy Evidence Database (PEDro)”, the articles were found in different languages but the articles more relevant were in English and Spanish. By means of the research was done the efficiency of the Myofascial release technique on the recovery of muscular contractures in soccer players demonstrated. The databases with the highest scientific performance were ResearchGate, Pub Med, Pubmed central and ScienceDirect. The articles collected were from the year 2013 to the year 2021. Completed the research by the respective discussion of the different authors, the planned objective to evidence the benefices of the Myofascial release technique and its action on the recovery of the muscular contractures on soccer players by collecting bibliographic information on the effects produced by this technique achieved. KEY WORDS: Fascia, Contracture, Hamstring Muscles, Myofascial Pain Syndromes Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324